Slightly water-soluble glass, slightly water-soluble glass product, composition, and method for improving water quality
Patent Information
- Application Number
- JP2021047821
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-22
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-03-22
AI Technical Summary
【0012】 本発明によれば、CuイオンやZnイオンを長期間にわたって溶出可能な緩水溶性ガラス、緩水溶性ガラス製品及び水質改善方法を提供することができる。 また、本発明によれば、上記の特徴を有する緩水溶性ガラス製品を製造可能な組成物を提供することができる。
Smart Images

Figure 0007645675000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a slightly water-soluble glass, a slightly water-soluble glass product, a composition, and a method for improving water quality. [Background technology]
[0002] In order to reduce the occurrence of mosquitoes that transmit infectious diseases such as dengue fever and Zika fever, it is desirable to suppress the occurrence and growth of mosquito larvae, which are the larvae of mosquitoes. Because mosquito larvae occur and grow in water that has been left unattended, various products made of copper or copper alloys that can elute copper (Cu) ions or zinc (Zn) ions into water to suppress the occurrence and growth of mosquito larvae have been proposed (Patent Documents 1 and 2).
[0003] It is also known that Cu ions and Zn ions are effective in inhibiting the growth of moss, algae, and the like, and antibacterial agents have been proposed in which oxides or hydroxides capable of eluting Cu ions or Zn ions are supported on porous substances such as porous glass (Patent Documents 3 and 4). Furthermore, Cu ions and Zn ions are known to be effective in imparting antibacterial and antiviral properties to glass, and glass products containing CuO and ZnO have been proposed (Patent Documents 5 and 6). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-216376 A [Patent Document 2] JP 2017-218406 A [Patent Document 3] JP 2003-81725 A [Patent Document 4] JP 2003-146818 A [Patent Document 5] Special Publication No. 2017-508705 [Patent Document 6] JP 2019-99514 A Summary of the Invention [Problem to be solved by the invention]
[0005] The various products described in Patent Documents 1 and 2 are made of solid copper or copper alloys, and therefore are not suitable for long-term use, for example, by being scattered on outdoor puddles, and their uses are limited. Furthermore, the antibacterial agents described in Patent Documents 3 and 4 are not sufficient in terms of their initial (immediately after use) antibacterial effect or their antibacterial effect over time (hereinafter referred to as "sustainability of antibacterial effect"). In particular, these antibacterial agents are not capable of eluting Cu ions or Zn ions for a long period of time. Furthermore, the glass products described in Patent Documents 5 and 6 do not dissolve entirely, so the effect does not last long enough. Also, since the glass products are difficult to dissolve, they are not suitable for use, for example, by scattering them on outdoor puddles, and their uses are limited.
[0006] The present invention has been made to solve the above-mentioned problems, and aims to provide a slightly water-soluble glass that is capable of eluting Cu ions and Zn ions over a long period of time, a slightly water-soluble glass product, and a method for improving water quality. Another object of the present invention is to provide a composition capable of producing a slightly water-soluble glass product having the above characteristics. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have discovered a glass composition that allows Cu ions and Zn ions to be gradually eluted as the glass melts, thereby completing the present invention.
[0008] That is, the present invention provides A glass having a low water solubility used as a growth inhibitor or repellent for pests, moss, and algae, an antibacterial agent, or an antiviral agent, The glass is slightly water-soluble and contains 40.0 to 75.0 mol % of SiO2, 5.0 to 38.0 mol % of K2O, 0.1 to 33.0 mol % of at least one selected from CuO and ZnO, and 28.0 mol % or less of R'O (R' is an alkaline earth metal), and does not contain B2O3.
[0009] The present invention also relates to a glass product having a slightly water-soluble glass as described above.
[0010] The present invention also relates to a composition containing the above-mentioned slightly water-soluble glass.
[0011] Furthermore, the present invention relates to a method for improving water quality, which comprises immersing the slightly water-soluble glass or the slightly water-soluble glass product in water and dissolving at least one type of ion selected from Cu ions and Zn ions into the water. Effect of the Invention
[0012] According to the present invention, it is possible to provide a slightly water-soluble glass capable of eluting Cu ions and Zn ions over a long period of time, a slightly water-soluble glass product, and a method for improving water quality. Furthermore, according to the present invention, there can be provided a composition capable of producing a slightly water-soluble glass product having the above-mentioned characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention.
[0014] The slightly water-soluble glass according to an embodiment of the present invention (hereinafter sometimes simply referred to as "glass") contains 40.0 to 75.0 mol % of SiO, 5.0 to 38.0 mol % of KO, 0.1 to 33.0 mol % of at least one selected from CuO and ZnO, and 28.0 mol % or less of R'O (R' is an alkaline earth metal).
[0015] In this specification, the term "slightly water-soluble glass" refers to glass that dissolves slowly in water. Specifically, the slightly water-soluble glass satisfies the following conditions in dissolution tests (normal and accelerated). (1) Regular Test In the normal test, the glass does not completely dissolve. The test is usually performed by immersing a piece of glass measuring 1 cm x 1 cm x 0.5 cm in 100 mL of distilled water at 20°C for 12 hours. (2) Acceleration testing The mass loss rate of the glass in an accelerated test is 2% or more. The mass reduction rate is calculated by the following formula. (Glass mass before accelerated test - Glass mass after accelerated test) / Glass mass before accelerated test x 100 The accelerated test is carried out as follows. First, the glass is crushed and then sieved into glass particles with a particle size of 1.4 to 2.0 mm, and the mass (mass of the glass before the accelerated test) is measured. Next, the sieved glass particles are immersed in 100 mL of distilled water at 90°C for 5 hours, and then sieved using a sieve with 0.5 mm openings. In the sieving, glass particles that have deteriorated and are no longer glass are crushed and removed. Next, the glass particles remaining on the sieve are dried, and the mass (mass of the glass after the accelerated test) is measured.
[0016] By making the glass slightly water-soluble, Cu ions and Zn ions can be gradually eluted as the glass slowly dissolves in water, making it possible to elute Cu ions and Zn ions into the water over a long period of time. Therefore, the effects of the Cu ions and Zn ions (for example, growth inhibition or repellent effects against pests such as mosquito larvae, mosses, algae, etc., antibacterial effects, and antiviral effects) can be maintained for a long period of time. The duration of the effect of Cu ions and Zn ions depends on the shape of the slightly water-soluble glass (particularly the surface area), the amount of water, the water temperature, etc., but for example, the effect can be sustained as long as the slightly water-soluble glass is visible. The duration of the effect can be appropriately set depending on the application of the slightly water-soluble glass, but can be adjusted so that it lasts for, for example, about 1 day to 10 years.
[0017] SiO2 is a component that forms the network structure of glass. If the SiO2 content is less than 40.0 mol%, the strength of the glass is insufficient. On the other hand, if the SiO2 content exceeds 75.0 mol%, the network structure becomes too strong. As a result, the dissolution rate of the glass decreases, so that Cu ions and Zn ions are not sufficiently dissolved in water, and the effect of Cu ions and Zn ions cannot be fully obtained. Therefore, from the viewpoint of stably securing the balance between the strength and dissolution rate of the glass, the SiO2 content is controlled to 40.0 to 75.0 mol%, preferably 42.0 to 72.0 mol%, and more preferably 43.0 to 70.0 mol%.
[0018] K2O is a component that increases the melting rate of glass. If the content of K2O is less than 5.0 mol%, the dissolution rate of the glass is decreased, so that Cu ions and Zn ions are not sufficiently dissolved in water, and the effect of Cu ions and Zn ions is not sufficiently obtained. On the other hand, if the content of K2O is more than 38.0 mol%, the dissolution rate of the glass becomes too fast, so that Cu ions and Zn ions cannot be dissolved for a long period of time. Therefore, from the viewpoint of ensuring an appropriate dissolution rate of the glass, the content of K2O is controlled to 5.0 to 38.0 mol%, preferably 7.0 to 37.0 mol%, and more preferably 9.0 to 36.0 mol%.
[0019] CuO and ZnO are components contained in the network structure of the glass and are dissolved as Cu ions and Zn ions when the glass is brought into contact with water. CuO and ZnO can be used alone or in combination. If the total content of CuO and ZnO is less than 0.1 mol%, the amount of Cu ions and Zn ions eluted in water is insufficient, and the effect of Cu ions and Zn ions cannot be obtained sufficiently. On the other hand, if the total content of CuO and ZnO exceeds 33.0 mol%, the glass tends to crystallize without being vitrified, which makes it difficult to dissolve in water and makes it difficult to control the amount of Cu ions and Zn ions eluted within an appropriate range. Therefore, the total content of CuO and ZnO is controlled to 0.1 to 33.0 mol%, preferably 0.5 to 32.0 mol%, and more preferably 0.8 to 31.0 mol%, from the viewpoint of ensuring a balance between the amount of Cu ions and Zn ions eluted and the solubility of glass.
[0020] When both CuO and ZnO are contained in the glass, the molar ratio of CuO to ZnO is not particularly limited, but is preferably 35:1 to 1:35, more preferably 10:1 to 1:10, and even more preferably 3:1 to 1:3. By controlling the molar ratio within such a range, it becomes possible to dissolve Cu ions and Zn ions in water in a well-balanced manner over a long period of time.
[0021] R'O (R' is an alkaline earth metal) is a component that improves chemical durability such as moisture absorption or water resistance of glass, and is contained in glass as necessary. R' is not particularly limited, but examples thereof include Mg, Ca, Sr, Ba, etc. R'O may be of a single type or of multiple types. If the R'O content exceeds 28.0 mol%, the glass becomes difficult to dissolve in water. Therefore, from the viewpoint of ensuring the solubility of the glass, the R'O content is controlled to 28.0 mol% or less, preferably 25.0 mol% or less, and more preferably 20.0 mol% or less. Since R'O does not necessarily have to be contained in the glass, the lower limit of the content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects of R'O, the lower limit of R'O is generally 0.1 mol%.
[0022] The slightly water-soluble glass according to the embodiment of the present invention may further contain known components that can be contained in glass as necessary, within the range that does not impair the effects of the present invention. Such known components are not particularly limited, but may include, for example, R2O (R is an alkali metal other than K) and Al2O3.
[0023] R2O (R is an alkali metal other than K) is a component that lowers the melting point and viscosity of glass, and is contained in glass as necessary. R is not particularly limited, but examples include Na, Li, Rb, and Cs. Among these, R is preferably Na or Li from the viewpoint of cost. R2O may be a single type or multiple types. If the R2O content exceeds 35.0 mol%, the glass becomes easily soluble in water. Therefore, from the viewpoint of ensuring the slow solubility of the glass, the R2O content is controlled to 35.0 mol% or less, preferably 33.0 mol% or less, and more preferably 31.0 mol% or less. Since R2O does not necessarily have to be contained in the glass, the lower limit of the content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects of R2O, the lower limit of R2O is generally 0.1 mol%.
[0024] Al2O3, like R'O, is a component that improves the moisture absorption or chemical durability, such as water resistance, of glass. If the content of Al2O3 exceeds 30.0 mol%, the glass becomes difficult to dissolve in water. Therefore, from the viewpoint of ensuring the solubility of the glass, the content of Al2O3 is preferably 30.0 mol% or less, more preferably 28.0 mol% or less, and further preferably 25.0 mol% or less. The lower limit of the content of Al2O3 is not particularly limited, but is generally 0.1 mol% from the viewpoint of obtaining the above-mentioned effects of Al2O3.
[0025] The slightly water-soluble glass according to the embodiment of the present invention preferably does not contain at least one selected from B2O3 and P2O5, and more preferably does not contain both B2O3 and P2O5. B2O3 and P2O5 are components that place a large burden on the environment. Therefore, by making glass with a composition that does not contain these components, the glass can be scattered outdoors in puddles and used for a variety of purposes. However, B2O3 and P2O5, like SiO2, are components that form the network structure of glass, and may be included in glass as necessary as long as the amount does not have an adverse effect on the environment. The amount of B2O3 and P2O5 that does not have an adverse effect on the environment is less than 0.5 mol% each.
[0026] The slightly water-soluble glass according to the embodiment of the present invention preferably has a specific gravity of 2.4 or more. By controlling the specific gravity within this range, for example, when the slightly water-soluble glass is used by scattering it in outdoor puddles, the slightly water-soluble glass can be made less likely to be washed away by rain or the like. The upper limit of the specific gravity is not particularly limited, but is preferably 10.0, more preferably 8.0, and even more preferably 5.0, taking into consideration the transportability of the slightly water-soluble glass. The specific gravity can be measured by a commercially available specific gravity meter using the Archimedes method.
[0027] The slightly water-soluble glass according to the embodiment of the present invention can elute Cu ions and / or Zn ions for a long period of time, and can therefore be used in various applications where it is desirable to obtain the effects of Cu ions and / or Zn ions for a long period of time. Examples of such applications include growth inhibitors or repellents for pests, mosses, algae, etc., antibacterial agents, antiviral agents, etc. Among these, growth inhibitors or repellents for pests, mosses, algae, etc. (especially mosquito larvae) are preferred.
[0028] The shape of the slightly water-soluble glass according to the embodiment of the present invention is not particularly limited, and can be appropriately set depending on the application. For example, when the slightly water-soluble glass itself is used as a growth inhibitor or repellent for pests, mosses, algae, etc., the slightly water-soluble glass may be formulated into an appropriate formulation. When the slightly water-soluble glass is used as a growth inhibitor or repellent by being blended with an existing agent such as a plant growth agent, the slightly water-soluble glass may be powdered and blended with the existing agent. Furthermore, when the slightly water-soluble glass is used as a raw material for molding materials, coating materials, etc., the slightly water-soluble glass may be powdered and blended with the molding materials or coating materials.
[0029] When the slightly water-soluble glass according to the embodiment of the present invention is used as a growth inhibitor or repellent for mosquito larvae, it is preferable to use it so that the concentration of Cu ions and / or Zn ions in the water is 0.5 ppm or more, preferably 1.0 ppm or more, more preferably 2.0 ppm or more. By making the concentration of Cu ions and / or Zn ions 0.5 ppm or more, it is possible to obtain a growth inhibitory effect or a repellent effect for mosquito larvae. In particular, if the concentration of Cu ions and / or Zn ions is 2.0 ppm or more, mosquito larvae hardly grow. The upper limit of the concentration of Cu ions and / or Zn ions is not particularly limited, and may be set appropriately according to environmental standards, etc.
[0030] The slightly water-soluble glass according to the embodiment of the present invention can be manufactured in the same manner as the known glass manufacturing method. That is, the slightly water-soluble glass according to the embodiment of the present invention can be manufactured by mixing the above-mentioned components to a predetermined content, heating to a high temperature to melt, and then forming the molten material into a predetermined shape (e.g., plate-like) and cooling. The molten material may be poured into a predetermined mold and cooled to be formed into a predetermined shape. In addition, when the slightly water-soluble glass is used as a raw material for a molding material or a coating material, the obtained slightly water-soluble glass may be pulverized into a powder.
[0031] The glass product having a slightly water solubility in water according to the embodiment of the present invention comprises the above-mentioned glass having a slightly water solubility in water. Since the glass product having a slightly water solubility in water comprises the above-mentioned glass having a slightly water solubility in water, Cu ions and Zn ions can be eluted for a long period of time. Therefore, the glass product having a slightly water solubility in water can obtain the effects of Cu ions and Zn ions (for example, growth inhibition or repellent effect against pests such as mosquito larvae, moss, algae, etc., antibacterial effect, antiviral effect) for a long period of time.
[0032] An example of a slightly water-soluble glass product according to an embodiment of the present invention is a coating product comprising a substrate and a coating layer formed on the surface of the substrate, the coating layer containing the above-mentioned slightly water-soluble glass. In the coating product, the slightly water-soluble glass is preferably dispersed in the coating layer. The substrate is not particularly limited, and may be one formed from metal, resin, or the like. Another example of the slightly water-soluble glass product according to the embodiment of the present invention is a resin molded product containing the above-mentioned slightly water-soluble glass. In the resin molded product, the slightly water-soluble glass is preferably dispersed in the resin.
[0033] The above-mentioned glass products having a slightly water-soluble property can be manufactured by using a composition containing the slightly water-soluble glass. For example, a coating product can be manufactured by using a composition containing the slightly water-soluble glass as a coating material and coating a substrate with the coating material. A resin molded product can be manufactured by using a composition containing the slightly water-soluble glass as a molding material and molding the molding material into a predetermined shape.
[0034] The composition used as the coating material may contain, in addition to the slightly water-soluble glass, known components used in coating materials (eg, resin components, solvents, inorganic components, etc.). The composition used as the molding material may contain, in addition to the slightly water-soluble glass, known components used in molding materials (eg, resin components, inorganic components, etc.).
[0035] In the water quality improvement method according to the embodiment of the present invention, the above-mentioned slightly water-soluble glass or the above-mentioned slightly water-soluble glass product is immersed in water to elute at least one ion selected from Cu ions and Zn ions into the water. According to this method, the elution of Cu ions and / or Zn ions can have a growth-inhibiting or repelling effect on pests such as mosquito larvae, mosses, algae, etc., thereby making it possible to improve the water quality.
[0036] The concentration of Cu ions and / or Zn ions eluted in water is not particularly limited, but is preferably 0.5 ppm or more, preferably 1.0 ppm or more, and more preferably 2.0 ppm or more. By setting the concentration of Cu ions and / or Zn ions eluted to 0.5 ppm or more, the above-mentioned effects can be obtained. The upper limit of the concentration of Cu ions and / or Zn ions eluted is not particularly limited, and may be appropriately set according to environmental standards, etc.
[0037] The amount of the above-mentioned slightly water-soluble glass or the above-mentioned slightly water-soluble glass product added to the water is not particularly limited, and may be appropriately set according to the amount of water so that a predetermined elution concentration of Cu ions and / or Zn ions can be maintained for a long period of time. EXAMPLES
[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0039] Each raw material was weighed and uniformly mixed under stirring to obtain the composition shown in Table 1. The mixture was heated at 1300-1450°C for 2-3 hours to melt, and the melt was then molded into a plate and cooled to obtain a plate sample. Samples Nos. 9, 10, 13, and 14 were crystallized without being vitrified, whereas the other test samples were vitrified. The plate samples thus obtained were evaluated as follows.
[0040] <Specific gravity> The specific gravity was measured using a specific gravity meter (MD-200S manufactured by Alpha Mirage Co., Ltd.).
[0041] <Dissolution test> As the dissolution test, the above-mentioned normal test and accelerated test were carried out. (1) Regular Test In the normal test, a piece of glass measuring 1cm x 1cm x 0.5cm was immersed in 100mL of distilled water at 20℃ for 12 hours. In the evaluation of this normal test, glass that was not completely dissolved was indicated as ◯, and glass that was completely dissolved was indicated as ×. Whether the glass was completely dissolved or not was determined by visual observation. (2) Acceleration testing After crushing the plate-shaped sample, the glass particles were crushed into glass particles having a particle diameter of 1.4 to 2.0 mm using a sieve, and the mass (mass of glass before the accelerated test) was measured. Next, the crushed glass particles were immersed in 100 mL of distilled water at 90°C for 5 hours, and then sieved using a sieve with a mesh size of 0.5 mm. The glass particles remaining on the sieve were thoroughly washed with distilled water. Next, the glass particles remaining on the sieve were dried, and the mass (mass of glass after the accelerated test) was measured. Then, the mass reduction rate of the glass was calculated using the above formula. In the evaluation of this accelerated test, a mass reduction rate of the glass of 2% or more was represented as ◯, and a mass reduction rate of the glass of less than 2% was represented as ×. The results of the above evaluations are shown in Table 1.
[0042] [Table 1]
[0043] As shown in Table 1, the samples of Test Nos. 2 to 8, 15, 19 to 21, and 23 to 24 (examples of the present invention) were determined to be slightly water-soluble glasses from the results of the dissolution test and contained a predetermined amount of CuO and / or ZnO. Therefore, these samples can gradually release Cu ions and / or Zn ions as the glass slowly dissolves in water. In contrast, the samples of Test Nos. 1, 16, and 17 (Comparative Examples) are water-soluble glass based on the results of the dissolution (normal) test. Therefore, in these samples, the glass immediately dissolves in water and Cu ions and / or Zn ions cannot be gradually eluted. In addition, the samples of Test Nos. 11, 12, 18, and 22 (Comparative Examples) are poorly water-soluble glasses based on the results of the dissolution (accelerated) test. Therefore, in these samples, the glass is poorly dissolved in water, and Cu ions and / or Zn ions cannot be gradually eluted. In addition, the samples of Test Nos. 9, 10, 13 and 14 (Comparative Examples) were crystallized without being vitrified, and therefore were considered not to be soluble in water, and therefore, these samples were unable to gradually elute Cu ions and / or Zn ions.
[0044] As can be seen from the above results, the present invention can provide a slightly water-soluble glass capable of eluting Cu ions and Zn ions for a long period of time, a slightly water-soluble glass product, and a method for improving water quality. The present invention can also provide a composition capable of producing a slightly water-soluble glass product having the above characteristics.
Claims
1. A slightly water-soluble glass used as a growth inhibitor or repellent for pests, mosses, and algae, an antibacterial agent, or an antiviral agent, 40.0 to 75.0 mol% SiO 2 and 5.0 to 38.0 mol% K 2 O, 0.1 to 33.0 mol % of at least one selected from CuO and ZnO, and 28.0 mol % or less of R'O (R' is an alkaline earth metal); B 2 O 3 Contains no mildly soluble glass.
2. 35.0 mol% or less of R 2 O (R is an alkali metal other than K), 30.0 mol % or less of Al 2 O 3 The slightly water-soluble glass according to claim 1 , further comprising at least one selected from the group consisting of:
3. P 2 O 5 The slightly water-soluble glass according to claim 1 or 2, which does not contain
4. The slightly water-soluble glass according to any one of claims 1 to 3, which has a specific gravity of 2.4 or more.
5. A glass product comprising the slightly water-soluble glass according to any one of claims 1 to 4.
6. A composition comprising the slightly water-soluble glass according to any one of claims 1 to 4.
7. The composition according to claim 6, which is a molding material or a coating material.
8. A method for improving water quality, comprising immersing the slightly water-soluble glass according to any one of claims 1 to 4 or the slightly water-soluble glass product according to claim 5 in water, and dissolving at least one type of ion selected from Cu ions and Zn ions into the water.
Citation Information
Patent Citations
Composition for antibacterial glass
JP1996245237A
Method for regenerating inorganic antimicrobial agent
JP2003081725A
Method for controlling pest with inorganic antimicrobial agent and method for improving water quality
JP2003146818A
antimicrobial borosilicate glass
JP2006520311A
Antibacterial glass and manufacturing method of the same
JP2014005194A